PULSE REDUCTION IN MANAGEMENT OF HYPERTROPHIC CARDIOMYOPATHY (TWO CLINICAL CASES) - N. S. Krylova; E. A. Kovalevskaya; N. G. Poteshkina; Е. A. Mershina; V. Е. Sinitsyn; N. A. Sonicheva; L. Monserrat (Российский кардиологический журнал, 2017)
Two clinical cases presented, of the patients with hypertrophic cardiomyopathy and individualized pulse reduction therapy approach. Patients were prescribed consequently bisoprolol and ivabradine (Coraxan®, “Les Laboratoires Servier”, France) with comparative efficacy assessment by a complex investigation that included EchoCG, exercise tests, 24-hour monitoring of ECG and BP.